FEATURES OF SOMATOTYPE COMPONENTS AND INDICATORS OF COMPONENT COMPOSITION OF BODY WEIGHT IN UKRAINIAN MEN AND WOMEN WITH MULTIPLE SCLEROSIS - Gunas, M.М.; Moskovko, G.S.; Ishchuk, O.H.; Oleksiienko, I.V.; Kyrychenko, V.I.; Gunas, I.V. (World of Medicine and Biology, 2025)
In Ukrainian young men and women with multiple sclerosis, compared with practically healthy men and women, numerous significant or trends in the differences in the components of the Heath-Carter somatotype (mainly in women) and indicators of the component composition of body mass were established. Most of the differences in the components of the Heath-Carter somatotype and indicators of the component composition of body mass between patients with multiple sclerosis with mild, moderate and moderately severe disorders were established in men. Pronounced manifestations of sexual dimorphism were established only for most indicators of the component composition of body mass (except for fat) between men with multiple sclerosis (larger values in the general groups and in the groups of patients with mild and moderately severe disorders) and women.
Keywords: nervous diseases; multiple sclerosis; somatotype; component composition of body mass; practically healthy and sick men and women